Glycerol restores p53-dependent radiosensitivity of human head and neck cancer cells bearing mutant p53 - Ohnishi, K (Nature Publishing Group, 2000)
Mutation or inactivation of p53 is known to be present in approximately 50% of human cancers. We propose here a novel strategy for overcoming this problem in mutant p53-targeting cancer therapies. We examined the restoration of radiation-induced p53-dependent apoptosis by a chemical chaperone (glycerol) in human head and neck cancer cells (SAS cells, showing wild-type p53 phenotype). SAS cells transfected with mutant p53 (SAS/m p53) showed radioresistance compared with SAS cells (SAS/ neo) transfected with neo vector as a control, but became radiosensitive when pre-treated with glycerol before X-ray irradiation. Apoptosis in the SAS/m p53 cells was induced by X-rays with glycerol pre-treatment, but not without glycerol pre-treatment, whereas apoptosis in the SAS/ neo cells was induced in both cases. Gel mobility-shift assays showed that after X-ray irradiation combined with glycerol pre-treatment, mp53 was able to bind to the sequence-specific region upstream of the bax gene regulating apoptosis. These results suggest that glycerol is effective in inducing a conformational change of p53 and restoring normal function to mp53, leading to enhanced radiosensitivity through the induction of apoptosis. This novel tool for enhancement of radiosensitivity in cancer cells bearing mp53 may be useful for p53-targeted radiotherapy. © 2000 Cancer Research Campaign http://www.bjcancer.com